(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study investigates customer perspectives towards online train ticket booking in the Thoothukudi district, focusing on user experiences, satisfaction levels, and the factors influencing their choices. Utilizing a mixed-methods approach, data were collected through surveys and interviews with local residents who frequently use online platforms for train ticket purchases. The findings reveal that while convenience and accessibility are primary motivators for using online booking systems, issues such as payment failures, customer service, and the accuracy of information significantly impact user satisfaction. The study concludes with recommendations for improving online ticketing services to enhance customer experiences in Thoothukudi.